Hair cortisol and testosterone concentrations and semen production of Bos taurus bulls. Issue 4 (2nd October 2017) - Stradaioli, Giuseppe; Peric, Tanja; Montillo, Marta; Comin, Antonella; Corazzin, Mirco; Veronesi, Maria Cristina; Prandi, Alberto
Abstract: The experiment was aimed to evaluate the usefulness of hair cortisol concentrations (HCC) in revealing the activation of the hypothalamic-pituitary-adrenal (HPA) axis due to the passage of young bulls from genetic rearing stations to artificial insemination (AI) centre and the influence of this passage on hair testosterone concentrations (HTC). Hair samples on 33 yearling bulls were collected at the time of arrival (ST1) to the AI centre and 3 more hair samples (ST2, ST3, ST4) were collected at monthly intervals. After the end of quarantine each animal was submitted to the standard procedures for collection and production of semen. Overall HCC were significantly affected by period of collection ( p < .01). In particular, HCC was higher in samples obtained after finishing the quarantine period (ST2) compared with those obtained on ST1. After ST2, the HCC decreased reaching at ST4 a value similar to that recorded at ST1. An effect of sampling time on HTC was not found ( p > .05). The effect of breed was observed only for HTC that was higher in PRI than BS ( p < .01). The HCC group have not influenced the semen variables ( p > .05). On the contrary, the effect of breed was evident. The results of this study replicated the effects of a major environmental stressor on mean cortisol concentrations assessed in hair, and add to the growing body of evidence that HCC is an effective and simply collected marker for long-term activity of the HPA system in response to persistent environmental challenge.